Population parameters and stock status of skipjack tuna Katsuwonus pelamis (Linnaeus, 1758) from Indian waters: stock status of skipjack tuna - Ghosh, Shubhadeep; Rohit, Pratibha; E. M. Abdussamad; U. Ganga; M. R. Margaret; S. Surya; H. M. Manas (Indian Journal of Fisheries, 2023)
Keywords: Catch rates, Exploitation, Growth, India, Katsuwonus pelamis, Landings, Mortality